Mengenal lebih jauh tulang sulbi Sebagai asal usul ‎penciptaan manusia melalui pendekatan al-Quran dan ‎fisiologi manusia - Sobach, Indah Nur (Maliki Interdisciplinary Journal, 2023)
One of the extraordinary wonders of God's creation is about the process of human creation. There are so many human creations that are alluded to in various studies, there is one organ that is alluded to in the Al-Quran, such as in Surah Al-A'raf verse 172 which states that what acts as the forerunner or origin of human creation is the sulbi bone which is a small part from the human spine. Integrated scientific studies are important to be carried out to prove the truth of the Al-Quran regarding the creation of humans. The method used in this study is the method of scientific interpretation, namely interpreting the verses of the Al-Quran through a scientific or scientific approach. Scientific research has proven that the tailbone (sulbi bone) does act as a way out for blood vessels and the nervous system which regulates the process of sperm or semen secretion as the forerunner of human formation. Through this integration study, it is hoped that we will be able to learn important lessons as well as take wisdom and lessons about God's greatness in each of His creations.Keywords: The coccyx, the creation of man, the integration of the Qur’an